Investigation on structural and magnetic properties of the mechanosynthesized Fe-doped ZrO2-15mol%Y2O3 - Sari Ali; Keddam Mourad; Ouanezar Abdelkader; Malki Abderrahim (Processing and Application of Ceramics)
Structure of ball-milled powder mixtures containing monoclinic zirconia (m-ZrO2) and 15mol% Y2O3 was analysed. It was shown that the tetragonal Zr0.85Y0.15O1.93 solid solution was formed within 30min of milling. The structural and magnetic properties were investigated using flame atomic absorption spectrometer, X-ray diffraction, Raman and Mössbauer spectroscopy. The study revealed an increase in fraction of the tetragonal Zr0.85Y0.15O1.93 phase with increasing iron impurity formed due to the wear in the stainless steel assembly. In the course of the ball-milling, the Fe3+ concentration increases with milling time promoting the formation of the paramagnetic Zr0.85(Y3+,Fe3+)0.15O1.93 solid solution. It has been found that there was no sign of tetragonal to metastable m-ZrO2 transition after annealing in the temperature range 500-1100°C keeping the tetragonal phase rich in Y3+ structurally stable. Taking into account the effect of the combined Fe3+ and Y3+ elements on structural features of the ball-milled product, Fe3+ cations promote the mobility of Y3+ and consequently diffuse into the tetragonal crystal lattice at room temperature, while Y3+ cations act as tetragonal stabilizers at high temperature.